Ethosomes and their monotonous effects on Skin cancer disruption - Shinde, Prafull; Page, Amit; Bhattacharya, Sankha (Frontiers in Nanotechnology, 2023)
Skin cancer is one of the most prominent diseases, affecting all continents worldwide, and has shown a significant rise in mortality and prevalence. Conventional therapy, including chemotherapy and surgery, has a few drawbacks. The ethosomal systems would be thoroughly reviewed in this compilation, and they would be classified based on constituents: classical ethosomes, binary ethosomes, and transethosomes. Ethosomes systems are model lipid vesicular carriers with a substantial portion of ethanol. The impacts of ethosomal system components, preparation techniques, and their major roles in selecting the final characteristics of these nanocarriers are comprehensively reviewed in this chapter. The special techniques for ethosomes, including the cold approach, hot approach, injection method, mechanical dispersion method, and conventional method, are explained in this chapter. Various evaluation parameters of ethosomes were also explained. Furthermore, ethosomal gels, patches, and creams can be emphasised as innovative pharmaceutical drug formulations. Some hybrid ethosomal vesicles possessing combinatorial cancer therapy using nanomedicine could overcome the current drug resistance of specific cancer cells. Through the use of repurpose therapy, phytoconstituents may be delivered more effectively. A wide range of in vivo models are employed to assess their effectiveness. Ethosomes have provided numerous potential skin cancer therapeutic approaches in the future.